An experimental study on the combined effects of n-hexane and toluene on the peripheral nerve of the rat. Issue 1 (February 1981) - Takeuchi, Y; Ono, Y; Hisanaga, N
Abstract : An electrophysiological study was undertaken to determine whether toluene affected the neurotoxicity of n-hexane. Separate groups of eight rats were exposed to 1000 ppm n-hexane, 1000 ppm toulene, 1000 ppm n-hexane plus 1000 ppm toluene, of fresh air in an exposure chamber for 12 hours a day for 16 weeks. The body weight, MCV, DL, MNCVs were measured before exposure, after four, eight 12, and 16 weeks exposure; and four weeks after exposure was discontinued. Exposure to 1000 ppm n-hexane considerably impaired the function of the peripheral nerve, but exposure to a mixture of 1000 ppm n-hexane plus 1000 ppm toluene resulted in only slight impairment; 1000 ppm toluene had little effect. These results strongly suggest that toluene decreases the toxic effects of n-hexane on the peripheral nerve.